1983
DOI: 10.1095/biolreprod28.1.196
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Maturation in Female Rats: Time-Related Changes in the Isoelectric Focusing Pattern of Anterior Pituitary Follicle-Stimulating Hormone 1

Abstract: Anterior pituitary glands (AP) were obtained from female rats at 5, 15, 18, 21 and 29 days of age, at the time of vaginal opening (VO) and during adulthood on proestrus. The multiple species of follicle-stimulating hormone (FSH) present within the AP were separated by the technique of polyacrylamide gel isoelectric focusing (PAG-IEF) and measured with the NIAMDD rat FSH radioimmunoassay kit. AP's obtained from immature female rats prior to VO contained elevated levels of total FSH as well as all of the species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…This is consistent with data from rats where an increase in bioactive forms of FSH within the pituitary was observed during the transition through puberty [96,97]. However, in heifers Stumpf et al [29] failed to detect a change in the distribution of either LH or FSH isoforms in pituitaries collected during sexual maturation.…”
Section: Factors Influencing Gonadotropin Isoform Profilesupporting
confidence: 88%
“…This is consistent with data from rats where an increase in bioactive forms of FSH within the pituitary was observed during the transition through puberty [96,97]. However, in heifers Stumpf et al [29] failed to detect a change in the distribution of either LH or FSH isoforms in pituitaries collected during sexual maturation.…”
Section: Factors Influencing Gonadotropin Isoform Profilesupporting
confidence: 88%
“…2 (Padmanabhan 1988;Wide and Naessen, 1994) and men (Matikainen et al, 1994 (Chappel et al, 1983;Wide 1989). Many studies using GnRH antagonists (Kessel et al, 1988;Mortola et al, 1989;Matikainen et al, 1992), GnRH agonist (Kessel et al, 1988) …”
Section: Resultsmentioning
confidence: 98%
“…It has been shown that gonadotropin isoforms influence a variety of biological activities, cellular growth and development, steroidogenesis and protein synthesis [37][38][39]. Because of their structural differences, FSH isoforms differ in their ability to bind to target cell receptors surviving in the circulation and induce a biological response in vivo and in vitro [40][41][42][43][44]. Evident differences between recombinant and urinary FSH were recognized, rFSH contains a higher proportion of less acidic isoforms, whereas urinary FSH contains a higher proportion of acidic forms.…”
Section: Discussionmentioning
confidence: 99%